Strategi Komunikasi Verbal Dan Nonverbal Dalam Meningkatkan Skill Public Speaking Santri SMK Life Skill Kendari - Mulyani, Sri Retno; Fauziah Muis, Sitti; Rahmawati, Rahmawati (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2022)
The students at the Kendari Life Skills Vocational School have various abilities in good public speaking. Some of the reasons found were that the process and period of practice for each student was different even though they received the same coaching. The coaching is done in theory and practice. These obstacles are trying to be overcome by coaching with verbal and non-verbal communication. This study aims to determine the verbal and non-verbal communication strategies of the coaches in improving the public speaking skills of the Kendari Life Skills Vocational High School students, including the supporting and inhibiting factors of the coaches in improving public speaking skills. The method used in this research is descriptive qualitative. The research design is based on the identified research variables and the hypotheses that will be tested for truth. In this study, data were collected using purposive and snowball sampling through data collection techniques. Testing the data through triangulation and qualitative inductive data analysis. This research was conducted at the Life Skill Vocational School of the Attarbiyatussakilah Islamic boarding school involving 17 respondents, namely 7 supervisors and 100 students. The results showed that the verbal and non-verbal communication strategies were effective enough to improve the public speaking skills of the Kendari Life Skills Vocational High School students. Based on research, between verbal and non-verbal communication found that verbal communication is more effective than non-verbal communication.